We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.

+0

# Algebra b

+1
429
6

.$$The/ function /f/ satisfies/ f(\sqrt{x + 1}) = \frac{1}{x} /for/ all/x \ge -1, x\neq 0. Find f(2).$$

2.$$Let/ f(x) = 3x^2 - 4x. Find/ the/ constant/ k/ such/ that/ f(x) = f(k - x) for/ all/ real /numbers/ x.$$

3.$$Find/ all/ complex /numbers/ z/ such /that/ z^2 = 2i. Write /your /solutions/ in/ a+bi /form/, separated/ by/ commas./ So,/ "1+2i, 3-i" /is/ an/ acceptable/ answer/ format,/ but/ "2i+1; -i+3"/ is/ not./ (Don't/ include/ quotes/ in/ your/ answer.)/ Note: /This/ problem /is /not /about/ functions.$$

4.

$$Let/ f/ be /a /function/ such/ that/ f(x+y) = x + f(y) /for/ any/ two/ real/ numbers/ x/ and/ y/. If f(0) = 2, then/ what/ is/ f(2012)?$$

Apr 12, 2018

### Best Answer

#1
+3

1.   The function  $$f$$  satisfies   $$f(\sqrt{x+1})=\frac1x$$   for all   $$x\geq-1\,,\quad x\neq0$$ .   Find  $$f(2)$$ .

We want to find an  x  value such that...

$$\sqrt{x+1}=2\\~\\ x+1=4\\~\\ x=3$$

So......

$$f(\sqrt{x+1})=\frac1x\\~\\ f(\sqrt{3+1})=\frac13\\~\\ f(\sqrt{4})=\frac13\\~\\ f(2)=\frac13$$

.
Apr 12, 2018
edited by hectictar  Apr 12, 2018

### 6+0 Answers

#1
+3
Best Answer

1.   The function  $$f$$  satisfies   $$f(\sqrt{x+1})=\frac1x$$   for all   $$x\geq-1\,,\quad x\neq0$$ .   Find  $$f(2)$$ .

We want to find an  x  value such that...

$$\sqrt{x+1}=2\\~\\ x+1=4\\~\\ x=3$$

So......

$$f(\sqrt{x+1})=\frac1x\\~\\ f(\sqrt{3+1})=\frac13\\~\\ f(\sqrt{4})=\frac13\\~\\ f(2)=\frac13$$

hectictar Apr 12, 2018
edited by hectictar  Apr 12, 2018
#2
+3

2.   Let   f(x)  =  3x2 - 4x  .  Find the constant  k  such that   f(x)  =  f(k - x)   for all real numbers  x .

f(x)   =   f(k - x)

And   f(x)  =  3x2 - 4x

3x2 - 4x   =   f(k - x)

And   f(k - x)  =  3(k - x)2 - 4(k - x)

3x2 - 4x   =   3(k - x)2 - 4(k - x)

3x2 - 3(k - x)2 - 4x + 4(k - x)   =   0

3[x2 - (k - x)2] - 4[x - (k - x)]   =   0

3[x + (k - x)][x - (k - x)] - 4[x - (k - x)]   =   0

3[x + k - x][x - k + x] - 4[x - k + x]   =   0

3[ k ][ 2x - k ] - 4[ 2x - k ]   =   0

( 2x - k )( 3k - 4 )   =   0

2x - k  =  0      or      3k - 4  =  0

k  =  2x                      k  =  4/3

The constant value that works is   k  =  4/3

Apr 12, 2018
edited by hectictar  Apr 12, 2018
edited by hectictar  Apr 12, 2018
edited by hectictar  Apr 12, 2018
#3
+1

Very nice, hectictar  !!!!   CPhill  Apr 12, 2018
#4
+2

Ah...thanks..but....my final answer happened to be right but my working out was all messed up!! I had to fix it!!

hectictar  Apr 12, 2018
#5
+1

I don't know....you're always pretty good with these function problems.....!!!   CPhill  Apr 12, 2018
#6
+2

4.   Let  f  be a function such that   f(x + y)  =  x + f(y)   for any two real numbers  x  and  y .

If  f(0)  =  2  ,  then what is  f(2012)  ?

f(x + y)  =  x + f(y)

f( -2012 + 2012 )   =   -2012 + f(2012)

f(0)   =   -2012 + f(2012)

2   =   -2012 + f(2012)

2 + 2012   =   f(2012)

2014   =   f(2012)

Apr 12, 2018